Nurses’ interest in lifelong learning - Głowacka, Mariola; Haor, Beata; Ślusarz, Robert; Biercewicz, Monika; Szewczyk, Edyta (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. The statutory duty of every nurse labor force is increasing qualifications by updating and expanding knowledge and skills. Aim. Aim of the study was presentation of the interests of nurses continuing education in terms of motives and factors limiting. Material and methods. The study was conducted in a group of 150 nurses in 2012, the method of diagnostic survey, the questionnaire technique using a questionnaire Results and conclusions. Tested nurses take a decision on postgraduate education guided by economic motives , their own ambitions, the  equirements of employers and improving the quality of services to patients and the prospect of changing jobs.